Biohydrogen Production from Palm Oil Mill Effluent Using Immobilized Mixed Culture - Singh, Lakhveer; Siddiqui, Muhammad Faisal; Ahmad, Anwer; Mohd Hasbi, Ab. Rahim; Mimi Sakinah, A. M.; Zularisam, A. W. (Elsevier, 2013)
Cell immobilization techniques were adopted to bio-hydrogen production using immobilized anaerobic sludge as the seed culture. Palm oil mill efï¬uent (POME) was used as the substrate carbon source. It was found that with a POME concentration of 20 g COD/l in the feed, the suspended-cell containing reactor was able to produce hydrogen at an optimal rate of 0.348 l H/(l POME h) at HRT 6 h. However, the immobilized-cell containing reactor exhibited a better hydrogen production rate of 0.589 l H2/(l POMEh), which occurred at HRT 2 h. When the immobilized-cell containing reactor was scaled up to 5 l, the hydrogen production rate was 0.500â0.588 l H/(l POME h) for HRT 2â10 h, but after a thermal treatment(60 8C, 1 h) the rate increase to 0.632 l H 22/(l POME h) at HRT 2 h. The main soluble metabolites were butyric acid and acetic acid, followed by propionic acid and ethanol.